Enhancing Teachers’ Productivity Through Differential Continuous Training in Edo State, Nigeria - Ekejiuba, Paulette (NIU Journal of Humanities, 2025)
The purpose of this paper is to investigate teachers’ differential continuous training as a correlate of teachers’ productivity. The paper also presented the various needs of teachers and their concerns as it relates to job productivity. To guide the study, four research questions were raised. Two were answered while others were formulated into hypotheses and tested at 0.05 level of significance. The study was a descriptive survey research. It adopted the correlational research design. The population consists of one thousand, seven hundred teachers in Edo State senior secondary schools. Ten percent of the population was employed as sample size which was one hundred and seventy senior secondary school teachers in Edo State. The research instrument was Likert type scale questionnaire consisting of fifteen items. The instrument was validated by three experts. Split-half reliability method was employed and Cronbach alpha reliability statistic was used to determine the reliability of the instrument. Data collected was analyzed using mean and standard deviation while hypotheses were tested using Pearson product moment correlation coefficient at an alpha level of 0.05 and the fisher’s Z statistic. The findings reveal that teachers have individual needs and problems in their teaching career. It was also discovered that there is no significant difference between teachers’ differential training and job productivity.  Teachers were to participate in in-service programs that address their needs. Teachers’ regular training should be funded to improve their productivity. Keywords: Teachers’ Productivity , Differential Continuous Training, Seasoned Teachers, Teaching Profession